Access to finance barriers affecting women owned SMMEs in the renewable energy sector: a case of South Africa - Mahwai, Matseba (Graduate School of Business (GSB), 2025)
The renewable energy industry has been acknowledged as one of the fastest-growing industries globally. Consequently, the industry presents various opportunities, not only for economic growth but for gender mainstreaming as well. This industry may serve as a means to address the shortcomings of the fossil fuel sectors and promote female representation. However, the industry is male-dominated, highlighting the importance of ensuring inclusive participation in the renewable energy sector to avoid replicating the structural inequalities and exclusionary practices historically observed in the fossil fuel industry. As such, it has become necessary for research to be undertaken to investigate financial barriers that are encountered by women- owned small, medium and micro enterprises (SMMEs) when venturing in the renewable energy industry. The study employed a qualitative approach, allowing participants to express and describe their lived experiences and opinions in terms of financial access barriers. The data was collected through online interviews from 12 women-owned SMMEs operating within the renewable energy sector across various provinces in South Africa. The thematic analysis of the interview data identified the following financial barriers faced by these SMMEs in venturing into the renewable energy sector: bureaucratic hurdles; early-stage risk aversion; lack of industry-tailored capital, high expected returns; lack of experience; lack of collateral; poor personal credit history; and perceptual barriers. Although some of the challenges faced by women-led SMMEs in the renewable energy sector are similar to challenges faced by SMMEs in other sectors, the uniqueness of this sector presents additional distinct barriers. Notably, traditional business evaluation methods are often applied, without tailoring these methods to align with the distinct characteristics of the industry. The findings from this study underscore the importance of reforms, particularly amongst the finance providers, to review their business evaluation method and ensure that they align with the distinctive nature of this critical industry. A review of women-targeted initiatives should be performed to ensure that the eligibility considers the financial barriers women face rather than reinforcing them. In addition, South Africa can learn from countries like India, who have implemented a centralised online portal that serves as a resource for accessing diverse financing schemes for renewable energy projects. A centralised online platform exclusively dedicated to facilitating access to finance for renewable energy projects can be created where entrepreneurs, particularly females, can access information on available support, webinars, and workshops.